Response of Rhodococcus cerastii IEGM 1278 to toxic effects of ibuprofen - Irina B. Ivshina; Elena A. Tyumina; Grigory A. Bazhutin; Elena V. Vikhareva (PLoS ONE, 2021)
The article expands our knowledge on the variety of biodegraders of ibuprofen, one of the most frequently detected non-steroidal anti-inflammatory drugs in the environment. We studied the dynamics of ibuprofen decomposition and its relationship with the physiological status of bacteria and with additional carbon and energy sources. The involvement of cytoplasmic enzymes in ibuprofen biodegradation was confirmed. Within the tested actinobacteria, Rhodococcus cerastii IEGM 1278 was capable of complete oxidation of 100 μg/L and 100 mg/L of ibuprofen in 30 h and 144 h, respectively, in the presence of an alternative carbon source (n-hexadecane). Besides, the presence of ibuprofen induced a transition of rhodococci from single- to multicellular lifeforms, a shift to more negative zeta potential values, and a decrease in the membrane permeability. The initial steps of ibuprofen biotransformation by R. cerastii IEGM 1278 involved the formation of hydroxylated and decarboxylated derivatives with higher phytotoxicity than the parent compound (ibuprofen). The data obtained indicate potential threats of this pharmaceutical pollutant and its metabolites to biota and natural ecosystems.